Faktor-Faktor Yang Mempengaruhi Keberhasilan Pemberian Asi Eksklusif - Tri Hastuti Lestari; Feva Tridiyawati (Malahayati Nursing Journal, 2022)
ABSTRACT WHO in 2020, said as many as 295,000 women worldwide lost their lives during and after pregnancy and childbirth. MMR in Indonesia in 2020 reached 230 per 100 thousand births. The direct cause of maternal death by 90% are complications during delivery and after delivery. Perineal rupture can occur due to spontaneous rupture or episiotomy. The impact of perineal rupture includes infection in the suture wound, and it can spread to the bladder tract. One of the efforts that can be done to prevent laceration of the perineum is perineal massage. Perineal massage is a technique of massaging the perineum during pregnancy or a few weeks before giving birth to increase blood flow to this area and increase the elasticity of the perineum. It is known the effectiveness of perineal massage on perineal rupture in labor. Quasi experimental with posttest only control group design. The sample in this study were all mothers who gave birth by normal delivery at BPM Tuti in January - February 2022 as many as 30 people, the sampling technique was total sampling. In the intervention group, most of the respondents did not experience perineal rupture (60%). In the control group, most of the respondents experienced perineal rupture (93.3%). There was an effectiveness of perineal massage on perineal rupture during labor (p value 0.001). There is an effectiveness of perineal massage against perineal rupture in labor. It is hoped that midwives will be more active in providing counseling to pregnant women to do perineal massage to prevent perineal rupture. Keywords : Perineal Rupture, Perineal Massage, Pregnancy ABSTRAK WHO pada tahun 2020, menyebutkan sebanyak 295.000 wanita di seluruh dunia kehilangan nyawa selama dan setelah kehamilan dan persalinan. AKI di Indonesia pada tahun 2020 mencapai 230 per 100 ribu kelahiran. Penyebab langsung kematian ibu sebesar 90% adalah komplikasi selama persalinan dan setelah melahirkan. Ruptur perineum dapat terjadi karena ruptur spontan atau episiotomi. Dampak ruptur perineum meliputi infeksi pada luka jahitan, dan dapat menyebar ke saluran kandung kemih. Salah satu upaya yang dapat dilakukan untuk mencegah laserasi perineum adalah pijat perineum. Pijat perineum adalah teknik memijat perineum selama kehamilan atau beberapa minggu sebelum melahirkan untuk meningkatkan aliran darah ke daerah ini dan meningkatkan elastisitas perineum. Telah diketahui efektifitas pijat perineum terhadap ruptur perineum pada persalinan. Eksperimen semu dengan desain posttest only control group design. Sampel dalam penelitian ini adalah seluruh ibu yang bersalin dengan persalinan normal di BPM Tuti pada bulan Januari – Februari 2022 sebanyak 30 orang, teknik pengambilan sampel adalah total sampling. Pada kelompok intervensi sebagian besar responden tidak mengalami ruptur perineum (60%). Pada kelompok kontrol, sebagian besar responden mengalami ruptur perineum (93,3%). Ada efektivitas pijat perineum terhadap ruptur perineum saat persalinan (p value 0,001). Ada efektivitas pijat perineum terhadap ruptur perineum pada persalinan. Diharapkan Bidan lebih aktif lagi memberikan konseling pada ibu hamil untuk melakukan pijat perineum supaya tidak terjadi ruptur perineum. Kata Kunci: Ruptur Perineum, Pijat Perineum, Kehamilan